Correction: Galenic lab-on-a-chip concept for lipid nanocapsules production. Issue 34 (20th August 2021) - Rolley, Nicolas; Bonnin, Marie; Lefebvre, Guillaume; Verron, Sylvain; Bargiel, Sylwester; Robert, Laurent; Riou, Jérémie; Simonsson, Carl; Bizien, Thomas; Gimel, Jean-Christophe; Benoit, Jean-Pierre; Brotons, Guillaume; et al.
Abstract : Correction for 'Galenic Lab-on-a-Chip concept for lipid nanocapsules production' by Nicolas Rolley et al., Nanoscale, 2021, 13, 11899–11912, DOI: ; 10.1039/D1NR00879J .